2023
DOI: 10.1002/adom.202300715
|View full text |Cite
|
Sign up to set email alerts
|

Yellow and Orange–Red Room‐Temperature Phosphorescence from Amorphous Nonaromatic Polymers

Abstract: Many nontraditional luminogens (NTLs) without any large π‐conjugated structures are reported to exhibit room‐temperature phosphorescence (RTP). Unfortunately, the reported NTLs mostly emit blue or green RTP. Achieving more redshifted RTP from NTLs remains a great challenge. Herein, a series of nonaromatic polymers exhibiting yellow and orange–red RTP are reported. Poly(itaconic anhydride) (PITA) does not exhibit RTP, its hydrolyzed product poly(itaconic acid) (PITAc) exhibits weak yellow RTP, but the ionized p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…The data show that through-space conjugation exists in the PUs. 56 Fig. S14 (ESI†) shows that there are a large number of hydrogen bonding interactions (such as C–H⋯OC, C–H⋯N and N–H⋯N), through-space dative bonds (carbonyl oxygen/ether oxygen to B atoms) and short contacts.…”
Section: Resultsmentioning
confidence: 99%
“…The data show that through-space conjugation exists in the PUs. 56 Fig. S14 (ESI†) shows that there are a large number of hydrogen bonding interactions (such as C–H⋯OC, C–H⋯N and N–H⋯N), through-space dative bonds (carbonyl oxygen/ether oxygen to B atoms) and short contacts.…”
Section: Resultsmentioning
confidence: 99%
“…87 Wang et al reported a series of nonaromatic amorphous polymers with yellow-orange-red RTP. Multiple nonaromatic donor−acceptor (nD-A) structures with carboxylate and lactam groups of different electron donor/ acceptor capabilities, combined with short contacts, aggregation, and efficient TSCT, collectively suppressed nonradiative decay, resulting in a reduction in the energy gap and an increase in the probability of intersystem crossing (ISC), and ultimately strong, orange-red RTP at ≈600 nm, with τ ph 41 ms. 88 Luminous hydrogels/organogels based on NCLMs are still rare and their mechanical properties are largely unexplored although they offer great potential for the development and applications of soft materials. Wang et al prepared high-strength hydrogels with RTP emission based on nonaromatic polymers.…”
Section: Room-temperature Phosphorescence (Rtp)mentioning
confidence: 99%
“…The following supporting information can be downloaded at: https: //www.mdpi.com/article/10.3390/molecules28165950/s1. Figure S1: 1 H NMR and 13 C NMR spectra of MAC. Figure S2: 1 H NMR and 13 C NMR spectra of MPB.…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…Figure S1: 1 H NMR and 13 C NMR spectra of MAC. Figure S2: 1 H NMR and 13 C NMR spectra of MPB. Figure S3: lifetime of MAC crystal under the excitation wavelength of 371.8 nm.…”
Section: Supplementary Materialsmentioning
confidence: 99%
See 1 more Smart Citation